Latihan Ladder Driil dan Ball Feeling terhadap Peningkatan Dribbling SSB Galaksi U13 - Rahman, Fathur; Annas, Mohamad (Universitas Negeri Semarang, 2023)
The purpose of the study was to determine the effect and test the ladder drill and ball feeling exercises on increasing dribbling ability. This type of research is a quantitative two pretest-posttest group design. The target of this study were students of SSB Galaxy U 13. The data analysis technique used the t test with a significant level of 5%. Research result; (1) value of t count (4,570> t table (2,262). Significance 0.000 < 0.05. It means Ho: rejected and Ha: accepted. There is an effect of ladder drill training on increasing dribbling. (2) the value of t count (4,709)> t table (2,262). Significance 0.000 < 0.05. It means Ho: rejected and Ha: accepted. There is an effect of ball feeling training on improving dribbling. The percentage increase in dribbling was obtained by ladder drill by 5,56%, while ball feeling exercise increased by 6,79%. It was concluded that the value of 5,56% < 6,79% hen the effect of ball feeling exercise was more effective than ladder drill exercise. Suggestions, coaches and athletes can use ball feeling training as a form of training program to improve dribbling abilities.